Innovative Mobile Solutions for Elevating Restroom Maintenance in Malaysian Shopping Malls - Bui Lin, Wee; Hui Hui, Wang; Poh Yin, Gan; Soo See, Chai (Semarak Ilmu Publishing, 2024)
Public toilets, crucial for our basic physiological needs, are often plagued by inadequate maintenance and poor hygiene, further exacerbated by their communal nature, which increases the risk of pathogen contamination, including SARS-CoV-2. Restroom hygiene significantly influences consumer choices and satisfaction when selecting shopping malls, impacting in-store spending. Furthermore, facility managers consistently identify restrooms as challenging to maintain. In Malaysia, public toilet cleanliness has long been a concern, with 20% receiving low ratings due to inadequate maintenance. Unfortunately, limited attention and resources are allocated to address these ongoing issues, as many mall restrooms still rely on inflexible paper-based management methods. Despite some technological solutions being introduced for public toilet management, they remain relatively novel and expensive in Malaysia, posing budgetary constraints for mall operators. Therefore, cost-effective solutions take precedence when implementing a new toilet management system. This research introduces an innovative, budget-friendly mobile-based system featuring an interactive panel with Raspberry Pi technology to revolutionize shopping mall toilet management. This mobile application allows supervisors to efficiently schedule cleanings, monitor progress, and assess cleanliness based on user feedback. Cleaning staff can promptly respond to user requests via the app, and users can request services and rate conditions. Usability tests reveal that 81% of users are satisfied with the system, meeting their expectations and enhancing operational efficiency. This comprehensive system facilitates effective communication among cleaning supervisors, cleaners, and users, ensuring consistently satisfactory restroom conditions. It promotes hygiene standards in shopping malls, which positively impacts both consumer perceptions and business outcomes for the malls.